On the interaction of risk and time preferences: An experimental study - Vital Anderhub; Uri Gneezy; Werner Güth; Doron Sonsino (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
Experimental studies of risk and time-preference typically focus on one of the two phenomena. The goal of this paper is to investigate the (possible) correlation between subjects' attitude to risk and their time-preference. For this sake we ask 61 subjects to price a simple lottery in 3 different scenarios. At the first, the lottery premium is paid now. At the second, it is paid later. At the third, it is paid even later. By comparing the certainty equivalents offered by the subjects for the three lotteries, we test how time and risk preferences are interrelated. Since the time interval between now and later is the same as between later and even later, we also test the hypothesis of hyperbolic discounting. The main result is a statistically significant negative correlation between subjects' degrees of risk aversion and their (implicit) discount factors.
urn:nbn:de:kobv:11-10046543
Keywords: 330